Analysis of Canonical Correlation Between Data of Asia, Europe and America Tourists with Tourism Spending in Thailand - Bunrangsee , Prinnaporn; Pasunon, Prasopchai (Business Administration and Management Journal Review, 2023)
The purpose of this research is to study the relationship between Asian, European and American tourist data and tourism spending in Thailand. By using the Canonical Correlation Analysis technique, the data used were statistics of the number of Asian, European and American tourists entering the country. Average number of stays per day Amount of expenditure per person and shopping, accommodation, and food and beverage expenses From January - June 2018 The results of the study showed that the canonical correlation between Asian tourist information. With the of 0.990 overall, it can account for a very high level of income (99.02%) in the Canonical correlation between European and American tourist data and spending. On the side with the of 0.998 overall, it can explain the data on the side income expenditure at a very high level (99.80%) as well. Tourism in Thailand of foreign tourists And can be developed into a tourism policy